Une question de pertinence : la Théorie Générale du temps de Keynes et aujourd’hui - Chick, Victoria (L'Actualité économique)

(untitled) (HEC Montréal, 1982)
AbstractThe author argues that there are six key assumptions — although they are at very different levels — on which the General Theory depends. These assumptions are: (i) unemployment is the norm; (ii) there is broad price stability; (iii) the money supply is quite inelastic; (iv) the capital stock and techniques are given; (v) the population is not growing substantially; and (vi) the capital stock is 'inadequate'. These six assumptions are all grounded in the British world of the interwar period that Keynes was looking at. Had the General Theory been written against the American background of the interwar or even the postwar periods, its assumptions would have looked purely analytical, instead of both analytical and empirically relevant.